2017
DOI: 10.12738/estp.2017.1.0378
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Portfolio Assessments on Metacognitive Skills and on Attitudes toward a Course

Abstract: Citation: Evin-Gencel, İ. (2017). The effect of portfolio assessments on metacognitive skills and on attitudes toward a course. AbstractThe aim of this study is to determine through teacher candidates' thoughts the effects of a portfolio assessment implementation on their metacognitive skills and attitudes towards a course on measurement and evaluation.Exploratory sequential mixed-methods design is employed within the study. The pretest/posttest control group design was used in the qualitative phase of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Teaching has additional challenges because it varies by classroom and group of students (Lin et al, 2005; Kramarski & Kohen, 2017); therefore, planning must also be flexible. Researchers have explored the role of metacognitive strategies among preservice teachers (Abd-El-Khalick & Akerson, 2009; Gencel, 2017; Kozikoglu, 2019; Kramarski & Kohen, 2017; Kramarski & Michalsky, 2009a; Kramarski & Michalsky, 2009b; Mok et al, 2006). For example, Mok et al (2006) found that the KWL method was effective in assisting preservice teachers in developing their knowledge structure and metacognition.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Teaching has additional challenges because it varies by classroom and group of students (Lin et al, 2005; Kramarski & Kohen, 2017); therefore, planning must also be flexible. Researchers have explored the role of metacognitive strategies among preservice teachers (Abd-El-Khalick & Akerson, 2009; Gencel, 2017; Kozikoglu, 2019; Kramarski & Kohen, 2017; Kramarski & Michalsky, 2009a; Kramarski & Michalsky, 2009b; Mok et al, 2006). For example, Mok et al (2006) found that the KWL method was effective in assisting preservice teachers in developing their knowledge structure and metacognition.…”
Section: Relevant Literaturementioning
confidence: 99%
“…"Empowering students as self-regulated learners is one of the fundamental goals in education" (Mak & Wong, 2017, p.12). When students think about their learning (Reynolds & Davis, 2014) and question how they know what they know (Hebert, 2001;Zhang, 2010a), they activate and develop their metacognitive skills (Apple, & Shimo, 2004;Gencel, 2016;Lam, 2015). Metacognition, which is defined simply as, "knowing what we know and how we have come to know it" (Hebert, 2001, p.51), contributes greatly to students' development as self-regulated learners (Negretti, 2012;Nilson, 2013), because it shows that "the individual knows the structure and functioning of his own cognitive system" (Coşkun, 2018, p.38).…”
Section: Some Of the Benefits Of Writing Portfolio Assessmentmentioning
confidence: 99%
“…Portfolio assessments are a collection of products created and completed by students, and they allows teachers, parents, students, and others to observe changes over time (Gencel, 2017). They are simply an evaluation of learning.…”
Section: Portfolio Assessmentmentioning
confidence: 99%
“…Portfolios have been seen as a way for parents, teachers, and students to view the student in a more positive, rather than negative, way (Stockall, Dennis, & Rueter, 2014). However, portfolios do reveal their mistakes and weaknesses (Gencel, 2017). Since work samples are included, teacher, parents, and students are able to evaluate their answers and mistakes made.…”
Section: Portfolio Assessmentmentioning
confidence: 99%